DILEMA KEAMANAN LIMA NEGARA DI KAWASAN ASIA TIMUR - MULIAWAN, ARIF ([Yogyakarta] : Universitas Gadjah Mada, 2015)
These theses titled “Security Dilemma’s of the Five States in Eastern Asia”. The main problem on these theses is “The response of the five states – China, Japan, South Korea, Taiwan, and North Korea – facing security dilemma‟s in the region by increasing both conventional and non-conventional military forces”. The main problem in this research based on the question: How every five states – China, Japan, South Korea, Taiwan, and North Korea – response and compete on increasing their defense capability? The range of this research focused on the events after Cold War period, especially after 9/11. The method which used on this research is qualitative method, by exploring literature sources which collected as available data. This research divide into five chapters, introduction, available data about increasing defense capacity of the five states which strengthened by theoretical view, the growing capacity of non-conventional military forces on every five states, the increase of conventional military power on every five states, and conclusion. According to research, there is some conclusion. First, every five states increase their defense capability for deterrence, which causing security dilemma on the region. Second, both China and North Korea growing their non-conventional military forces by deploying ballistic missiles and nuclear weapons, while Japan, South Korea, and Taiwan, grow their non-conventional military forces by building anti-missile defense system. Third, China increasing conventional military forces by produce new armaments on their navy and air forces, such as aircraft carrier, submarines, and stealth fighter jets, while North Korea maximize their submarines and mine layer fleet capability for their navy, and deploy drones for their air forces, for Japan, South Korea, and Taiwan, increasing their conventional military forces by upgrading their anti-submarine warfare capability and produce and producing new warships, such as destroyers and submarines for their navy, and deploying or bought stealth fighter jets for their air forces.